Penerapan Metode Distribution Requirement Planning (DRP) dalam Meminimalisasi Biaya Distribusi pada Perusahaan Jasa Pergudangan - Putri, Anindya Nurarta; Winarno, Winarno; Alifin, Fakhri Ikhwanul (Universitas Indraprasta PGRI Jakarta, 2025)
Distribution Requirement Planning (DRP) is a method used in the planning process that utilizes customer demand information, inventory stock, and production capacity to plan and schedule product distribution more accurately. This research aims to delve deeper into the issues faced by Warehousing Service Companies in distribution scheduling and how the DRP method can be an effective solution. With a deep understanding of this issue, it is expected that the company can improve their distribution performance, reduce operational costs, and enhance customer satisfaction. This research uses the Distribution Requirement Planning (DRP) method and utilizes data obtained from a health product warehousing service company. Based on the research conducted, the forecast of health product demand for the next 3 months was obtained as the standard requirement that the company must meet. In addition, the use of the Distribution Requirement Planning (DRP) method was able to reduce warehousing service costs by 29% compared to the method previously used by the company.